Analisis Pengaruh Kontrol PI Dengan Integral Anti-Windup Sebagai Upaya Reduksi Lonjakan Respon pada Sistem Ruang Termal - Reza Fauzi Iskandar; Reksa Putra; Asep Suhendi (Komputika : Jurnal Sistem Komputer, 2019)
The Proportional Integral Derivative (PID) control is a classical control type which still use in industry and the development of methods is being improve. The simplicity of the structure and reliability of the PID makes this control more popular in the industry. Integral element is control element that produce control signals by accumulating error, its process can cause the windup events. Windup is the accumulation of integral controls outside the saturation boundary. Windup has an impact on forced response over a long period which worsens of time response and stability. This paper examines the application of anti-windup controls as an effort to overcome the accumulation of integral actions in PI control scheme. At the temperature reference value of 35 0C, the room temperature response with anti-windup shows a high temperature overshoot about 43.6%. The settling time is 15.3 minutes relative slow. The system response with anti-windup shows the lowest temperature overshoot that is 15.2% and the settling time of the system tends to be faster around 6.9 minutes. Keywords – Thermal room, proportional-Integral, anti-windup.